2015
DOI: 10.1016/j.marchem.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Probing the photochemical reactivity of deep ocean refractory carbon (DORC): Lessons from hydrogen peroxide and superoxide kinetics

Abstract: Most marine DOC is thought to be biologically-recalcitrant, especially that in the deep ocean pool (N 1000 m). In particular, the deep waters of the North Pacific should contain the most recalcitrant DOC because they do not form locally, with deep DOC having survived long isolation from the surface during global-scale thermohaline circulation. One of the proposed removal pathways involves photochemical reactions when refractory DOC circulates through sunlit surface waters (Mopper et al., 1991). Here, we reeval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 66 publications
4
41
0
Order By: Relevance
“…Samples were filtered either directly from Niskin bottles or pumped through 0.2 µm filters (Whatman; Polycap-75AS) into 10 or 20 L acid-cleaned polyethylene carboys (Nalgene) and stored at 4 • C until use, for a period of up to 1 month. Our experience indicates that storage for seawater samples does not impact sample optics or the photochemical production rates for H 2 O 2 (Powers et al, 2015). While all equipment in contact with seawater samples was acid cleaned as described above and nitrile gloves were used in handling samples, the R/V Savannah and the laboratory was not equipped with special trace metal processing facilities and thus, limited trace metal contamination could be present.…”
Section: Sample Collection and Handlingmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples were filtered either directly from Niskin bottles or pumped through 0.2 µm filters (Whatman; Polycap-75AS) into 10 or 20 L acid-cleaned polyethylene carboys (Nalgene) and stored at 4 • C until use, for a period of up to 1 month. Our experience indicates that storage for seawater samples does not impact sample optics or the photochemical production rates for H 2 O 2 (Powers et al, 2015). While all equipment in contact with seawater samples was acid cleaned as described above and nitrile gloves were used in handling samples, the R/V Savannah and the laboratory was not equipped with special trace metal processing facilities and thus, limited trace metal contamination could be present.…”
Section: Sample Collection and Handlingmentioning
confidence: 99%
“…An assumption of all AQY calculations based on a single time point measurement is that the product is generated as a linear function of photon dose. With these experiments, as done in Powers and Miller (2014), it is unclear whether this requirement is met, especially when a lack of reciprocity for H 2 O 2 photoproduction over irradiation time has been reported elsewhere (Kieber et al, 2014;Powers et al, 2015). Results of SOD addition experiments were also variable in this study, so a 2:1 stoichiometry between O − 2 and H 2 O 2 was assumed and O − 2 photoproduction rates were predicted using this stoichiometry together with the AQY for H 2 O 2 .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Aside from biodegradation, DOM is also subject to photochemical processing in the photic zone, leading to bleaching of chromophoric DOM (CDOM), direct mineralization (DOC loss), and production of biolabile or bio‐refractory organic matter (Moran & Zepp, 1997; Obernosterer et al, 1999). Despite being physically limited to the sunlit layer, photooxidation may affect DOM cycling within the entire water column, given that the average radiocarbon age of DOC in the deep ocean is far longer than the turnover times of the ocean (centuries to one millennium), allowing the old DOC to circulate between the surface and deep oceans multiple times during its lifetime (Mopper et al, 1991; Powers et al, 2015). The photoreactivity of DOM may, however, be depth dependent due to dissimilar chemical compositions of DOM at different depth regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Medeiros et al (2015) revealed that the molecular signatures of DOM in the deep water of the Gulf of Alaska become more similar to that in surface water after irradiation. The photoreactivity of the deep RDOM in that region is nevertheless comparable to or lower than that of DOM in surface water in terms of hydrogen peroxide and superoxide photoproduction (Powers et al, 2015). Fluorescent DOM (FDOM) in deep water from the Bermuda Atlantic Time‐series Study (BATS) site, however, photo‐decomposes considerably faster than does FDOM in surface water (Timko et al, 2015).…”
Section: Introductionmentioning
confidence: 99%